A Networked Intelligent Distributed Virtual Training Environmnet:A First Approach - Christos Bouras; Thrasivoulos Tsiatsos; A Philopoulos (5th Joint Conference on Information Sciences-JCIS 2000-1st International Workshop on Intelligent Multimedia Computing and Networking, Taj Mahal, Atlantic City, New Jersey, USA, Vol. 2, 2000)
Collaborative livelong learning is one of the emerging needs of the information age. Access to education is going to become crucial for the success of our information society. Therefore a lot of potential is seen in distance learning and online collaborative environments. This paper proposes an intelligent distributed virtual training environment for distance education through shared 3D spaces